Análisis exploratorio sobre el fracturamiento hidráulico realizado en el Pozo Akira 14 ubicado en Villanueva, Casanare; las herramientas empleadas y su método de operación por parte de la subdivisión de completamiento de pozos Testing & Subsea – Halliburton. (2024)
In this thesis, the fundamentals of the hydraulic fracturing reservoir stimulation technique will be described. Additionally, the tools supplied by the well completion subdivision of Testing & Subsea – Halliburton will be identified and their mode of operation will be determined to carry out the hydraulic fracturing of the Akira 14 well located in Villanueva, Casanare, Colombia in March 2022. Through holding various meetings and interviews with engineers from the Testing & Subsea area, added to in-person visits to Halliburton – Base Cota, various calculations will be carried out that will allow the performance and operation of the tools to be determined assertively in each and every one of them. the stages for the correct execution of hydraulic fracturing.